KARAKTERISASI SIFAT KEMAGNETAN PASIR BESI PANTAI PUNTARU KABUPATEN ALOR-NTT - Martasiana Karbeka; Faryda Veronica Lamma Koly; Nini Mau Tellu (Lantanida Journal, 2020)
Iron sand is a source of natural magnetic material which is quite abundant. Iron sand can be useful as a magnetic source material which has the potential as a raw material for using magnetic materials. Iron sand contains non magnetic minerals which can reduce its magnetic properties. Therefore, iron sand sample preparation was carried out by washing NaOH 0,4 M and sand sample size variations. The purpose of this study was to determine the effect of washing and the size of iron sand on the magnetic properties in terms of the increase in magnetic elements. The results of research with XRF (X-Ray Fluoresence) show that iron sand with a size of 120 mesh has a magnetic content of Fe (78.07%) higher than iron sand with a size of 80 mesh with Fe content (34.63%). XRD (X-Ray Diffraction) analysis shows that washing iron sand with a size of 80 mesh gives a quarts phase (SiO2) at 2θ = 27.62° and iron sand washing with a size of 120 mesh gives the main peak magnetite phase (Fe3O4) at 2θ = 30.69° with a crystallinity of 15%. VSM (Vibrating Sample Magnetometer) analysis depicted on the hysteresis curve shows that the smaller the particle size of iron sand, the higher the magnetic properties. There are still minor oxides in iron sand as  oxide minerals.